Revitalisasi Gabungan Organisasi Wanita (GOW) Dalam Pembentukan Buku Profil Dan Media Sosial Sebagai Upaya Pengembangan Kapasitas Organisasi Wanita Di Kota Salatiga Tahun 2021 - Daru Purnomo; Garcian Gracias Purba; Irene Iriani Pah; Maura Kinsa Tsabitha; Monica Biola Gunawan (Universitas Kristen Satya Wacana Salatiga, 2021)
An organization must stand by having a strong foundation in order to achieve the goals that are used as directions for the establishment of the organization. It is also owned by the Association of Women's Organizations (GOW) Salatiga. Along with the age of an organization and the times, organizational revitalization is very necessary for the purpose of developing the capacity of the organization and it is also very important to do so that the organization has a track record in the process. One form of revitalization is the design of a GOW profile book which contains a brief history and activities that have been carried out by GOW and its 25 elements along with photos of activities so that they can be used as track records in the process. The profile book can also be used as an archive of GOW in finding data related to the previous activities of its 25 elements